Cohnella sp. A01 laccase: thermostable, detergent resistant, anti-environmental and industrial pollutants enzyme - Shafiei, Masoomeh (Heliyon, 2019)
Laccase (EC 1.10.3.2; benzenediol; oxygen oxidoreductases) is a multi-copper oxidase that catalyzes the oxidation of phenols, polyphenols, aromatic amines, and different non-phenolic substrates with concomitant reduction of O(2) to H(2)O. Enzymatic oxidation techniques have the potential of implementation in different areas of industrial fields. In this study, the Cohnella sp. A01 laccase gene was cloned into pET-26 (b+) vector and was transformed to E. coli BL21. Then it was purified using His tag affinity (Ni sepharose resin) chromatography. The estimated molecular weight was approximately 60 kDa using SDS-PAGE. The highest enzyme activity and best pH for 2,6-dimethoxyphenol (DMP) oxidation were recorded as 8 at 90 °C respectively. The calculated half-life and kinetic values including K(m), V(max), turn over number (k(cat)), and catalytic efficiency (k(cat)/K(m)) of the enzyme were 106 min at 90 °C and 686 μM, 10.69 U/ml, 20.3 S(−), and 0.029 s(−1) μM(−1), respectively. The DMP was available as the substrate in all the calculations. Enzyme activity enhanced in the presence of Cu(2+), NaCl, SDS, n-hexane, Triton X-100, tween 20, and tween 80, significantly. The binding residues were predicted and mapped upon the modeled tertiary structure of identified laccase. The remaining activity and structural properties of Cohnella sp. A01 laccase in extreme conditions such as high temperatures and presence of metals, detergents, and organic solvents suggest the potential of this enzyme in biotechnological and industrial applications. This process has been patented in Iranian Intellectual Property Centre under License No: 91325.